The Effect of Employee Resilience, Work Flexibility, and Gamification Training Program as Intervening Variables on Employee Performance - Uli Artha, Citra; Sitorus, Sunday Ade; Nopeline, Nancy; SUNDAY ADE SITORUS (Manunggal Halim Jaya, 2025)
This study aims to determine how the influence of employee resilience, work flexibility, and gamification training programs as intervening variables on employee performance at PT Nusareka Prima Engineering. This research uses quantitative methods with incidental sampling techniques and involves 109 respondents as samples. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software version 4.0. The results showed that employee resilience did not have a significant effect directly on employee performance, with a significance level of 0.074 (>0.05). However, work flexibility has a significant direct effect on gamification training programs with a significance level of 0.005 (<0.05), although work flexibility has no direct effect on employee performance (0.566 > 0.05). Gamification training program as an intervening variable significantly affects employee performance with a significance level of 0.002 (<0.05). Employee resilience through the gamification training program also significantly affects employee performance with a significance level of 0.041 (<0.05). Work flexibility through the gamification training program significantly affects employee performance with a significance level of 0.028 (<0.05). This study concludes that the gamification training program is an important intervening variable in improving employee performance. Work flexibility has a significant influence on the success of the gamification training program, which has an impact on improving employee performance.